2012
DOI: 10.1002/zaac.201100515
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of NCN‐Chelated Organobismuth(III) Bis‐Pentasulfide

Abstract: Organobismuth(III) sulfide (1) containing the NCN pincer type chelating ligand L {L = [2,6-(CH 2 NMe 2 ) 2 C 6 H 3 ] -} reacts with one molar equivalent of elemental sulfur to give the unprecedented cyclic bis-pentasulfide LBi(μ-S 5 ) 2 BiL (2) with the central twelve-membered * Dr. L. Dostál Fax: +420-466037068 E-Mail: libor.dostal@upce.cz [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The authors ascribe the elongated bond length to a polarized BiÀ S bond, with the positive charge at the bismuth atoms being stabilized by the pincer ligand. [60] The CÀ BiÀ S angles around the bismuth atom are similar as in the previously discussed Dipp substituted structures (Dipp 2 BiX, X=Cl, Br) with each Bi atom showing one small (3 a: 94.3(1 5pm, far larger than the sum of the van der Waals radii (414 pm), [49] indicating no interaction between the bismuth atoms.…”
Section: Single Crystal X-ray Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…The authors ascribe the elongated bond length to a polarized BiÀ S bond, with the positive charge at the bismuth atoms being stabilized by the pincer ligand. [60] The CÀ BiÀ S angles around the bismuth atom are similar as in the previously discussed Dipp substituted structures (Dipp 2 BiX, X=Cl, Br) with each Bi atom showing one small (3 a: 94.3(1 5pm, far larger than the sum of the van der Waals radii (414 pm), [49] indicating no interaction between the bismuth atoms.…”
Section: Single Crystal X-ray Analysissupporting
confidence: 78%
“…An example for a longer Bi−S bond than in 3 b is described in one compound of the form RBi‐(S 5 ) 2 ‐BiR (R=o‐(CH 2 NMe 2 ) 2 C 6 H 3 ) showing a twelve membered Bi 2 S 10 ring, stabilized by NCN‐type pincer ligands at the bismuth atoms (Bi−S: 275–277 pm). The authors ascribe the elongated bond length to a polarized Bi−S bond, with the positive charge at the bismuth atoms being stabilized by the pincer ligand [60] . The C−Bi−S angles around the bismuth atom are similar as in the previously discussed Dipp substituted structures (Dipp 2 BiX, X=Cl, Br) with each Bi atom showing one small ( 3 a : 94.3(1)°, 90.7(1)°; 3 b : 90.2(2)°) and one larger ( 3 a : 108.2(1)°, 110.2(1)°; 3 b : 104.5(1)°) angle due to steric repulsion of the polysulfide chain and one Dipp substituent.…”
Section: Resultsmentioning
confidence: 99%
“…Arylbismuth sulfide (LBiS) 2 can also be used in organoelement synthesis. For instance, (LBiS) 2 containing the NCN-chelating ligand L = 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 reacts with one molar equivalent of elemental sulfur to form cyclic bis(pentasulfide) LBi(μ-S 5 ) 2 BiL with the central 12-membered ring Bi 2 S 10 (Scheme 128) [127].…”
Section: Scheme 127mentioning
confidence: 99%
“…This is the only example of a bismuth-benzyl compound in the literature, despite the fact that benzyl is a special type of alkyl group that can coordinate in a variety of ways to metals, Scheme . To determine how bismuth benzyl complexes compared structurally to BiPh 3 and Bi(allyl) 3 complexes, the reactions of a benzyl Grignard reagent with bismuth chlorides were explored. The reaction with the NCN pincer aryl ligated complex, Ar′BiCl 2 [Ar′ = 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 ], was studied first because this ancillary Ar′ ligand has proven useful in isolating many new types of complexes. The homoleptic complex, Bi(CH 2 Ph) 3 , , was synthesized for crystallographic studies and the results are reported here.…”
mentioning
confidence: 99%